Optimizing the Intellectual Property Rights as Banking Credit Collateral by Art Workers in Karawang - Tri Setiady; R. Siti Sumartini; Meita Fadhilah; Erdin Tahir (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
As proprietors of Intellectual Property Rights (IPR), creative professionals (designers, creators, and inventors) in Karawang regency own exclusive rights that enable them to independently profit from their works in the form of royalties or licensing. However, in reality, they have difficulties in accessing capital needed to expand their business. Some financial institutions might not accept IPR as collateral for credit even though the law principally states that they are valuable assets and therefore eligible as collateral. Copyright Law No. 28 of 2014 (Article 16) and Patent Law No. 13 of 2016 (Article 108) both permit owners and holders of intellectual property rights to utilize such rights as collateral for loans under a fiduciary arrangement. The laws should apply to copyrights and patents, but so far they haven't, which is a shame because in theory they should. The lack of a change to Article 43 of BI Regulation Number 14/15/PBI/2012, which pertains to the forms of credit collateral, makes it difficult to use intellectual property rights as security for loans. To make the concept relevant, the regulation has to be changed